CONSTITUCION QUIMICA DEL GENE Y ESPECULACIONES SOBRE SU COMPORTAMIENTO NORMAL Y PATOLOGICO - SALAZAR MALLEN, MARIO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1947)
Various staining methods (Cajal, Herxheimer, and Nieto) were applied to prepns of the brain of the cat, dog, and human Impregnation methods showed in young animals a canalicular structure which gave no trace of the presence of lipoids and was considered
BOL INST ESTUD MED BIOL
Keywords: CONSTITUCION, QUIMICA, GENE, COMPORTAMIENTO, PATOLOGICO; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA